2016
DOI: 10.3126/jnps.v35i3.14004
|View full text |Cite
|
Sign up to set email alerts
|

Morbidities and Mortalities among Infant of Diabetic Mother in a Newly Established Scabu of a Tertiary Care Hospital, Bangladesh

Abstract: Introduction: Diabetes mellitus has long been associated with perinatal morbidity and mortality. It complicates 2% to 3% of all pregnancies; 90% of these cases present with gestational diabetes mellitus. In our population Gestational diabetes mellitus develops among 6.7% of all pregnancies. Macrosomia (28%), hypocalcaemia (22%), hyperbillirubinaemia (19%), polycythemia (34%), perinatal asphyxia, birth injury and congenital anomaly (6-9%) are the complications of infant of diabetic mother (IDM). Materials and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Six studies 8,9,25–28 showed that higher percentage of pregnant women with GDM have a foetal outcome of macrosomia compared to women with no GDM. Akhter et al 23 and Islam et al 24 reported that macrosomia was highly prevalent among GDM mother, although the findings were inconclusive due to lack of a control group.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies 8,9,25–28 showed that higher percentage of pregnant women with GDM have a foetal outcome of macrosomia compared to women with no GDM. Akhter et al 23 and Islam et al 24 reported that macrosomia was highly prevalent among GDM mother, although the findings were inconclusive due to lack of a control group.…”
Section: Resultsmentioning
confidence: 99%
“…All the studies were conducted in hospital settings except one study which was carried out in rural areas of Assam, India 26 . In five studies, GDM was diagnosed in accordance with the WHO criteria and was measured performing an oral glucose tolerance test (OGTT), 9,23,25–27 while in other studies ( n = 3), patient recall were used 8,24,28 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations